2010
DOI: 10.1111/j.1399-3046.2009.01141.x
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of the metabolic syndrome and associated left ventricular hypertrophy in pediatric renal transplant recipients

Abstract: metabolic syndrome is common at time of pediatric kidney transplant, and prevalence rises sharply at one-yr post-transplant. The presence of metabolic syndrome is strongly associated with LVH in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
53
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(58 citation statements)
references
References 28 publications
4
53
1
Order By: Relevance
“…93 A study from the Midwest Pediatric Nephrology Consortium using data from six centers determined that 68% of children with healthy weight and 80% of overweight/obese children had uncontrolled BP ($95th percentile for age, sex, and height) 1 year after transplantation. 94 Similarly, recent data from the ESPN/ERA-EDTA registry on BP control among pediatric ESRD patients in Europe confirmed a high rate of hypertension in pediatric transplant recipients: hypertension was diagnosed in 66.9% with more than one-third having elevated BP despite being on antihypertensive therapy. 95 Sinha et al 96 conducted a retrospective analysis of all current pediatric kidney transplant patients in the United Kingdom, with data collected at 6 months and 1, 2, and 5 years after transplantation: the rate of uncontrolled hypertension has been unchanged (25%-27%) during follow-up.…”
Section: Hypertension In the Pediatric Transplant Recipient Or Recipimentioning
confidence: 89%
“…93 A study from the Midwest Pediatric Nephrology Consortium using data from six centers determined that 68% of children with healthy weight and 80% of overweight/obese children had uncontrolled BP ($95th percentile for age, sex, and height) 1 year after transplantation. 94 Similarly, recent data from the ESPN/ERA-EDTA registry on BP control among pediatric ESRD patients in Europe confirmed a high rate of hypertension in pediatric transplant recipients: hypertension was diagnosed in 66.9% with more than one-third having elevated BP despite being on antihypertensive therapy. 95 Sinha et al 96 conducted a retrospective analysis of all current pediatric kidney transplant patients in the United Kingdom, with data collected at 6 months and 1, 2, and 5 years after transplantation: the rate of uncontrolled hypertension has been unchanged (25%-27%) during follow-up.…”
Section: Hypertension In the Pediatric Transplant Recipient Or Recipimentioning
confidence: 89%
“…However, the etiology of CKD in children is different than in adults; congenital abnormalities of the urinary tract account for most cases of pediatric CKD, whereas hypertensive and diabetic nephropathy, the leading causes of CKD in adults, are quite rare in children. Despite this difference in etiology, up to 21% of children have multiple CVRF at time of transplant, with 40% of patients affected at 1 year post transplant (21). There are few published data regarding prevalence and disease-specific correlates of multiple CVRF in children with earlier stages of CKD.…”
Section: Introductionmentioning
confidence: 98%
“…For example, a recent multicenter study determined that 38% of kidney transplant recipients had at least three traditional cardiovascular risk factors. 21 …”
Section: Traditional Risk Factorsmentioning
confidence: 99%
“…Data from the International Pediatric Peritoneal Dialysis Network registry 31 on 507 patients report the overall prevalence of LVH to be 48%. A Midwest Pediatric Nephrology Consortium study, 21 utilizing data from six centers, demonstrated the prevalence of LVH to be 40% in children 1-year post-transplant. Most of these studies show the persistence of cardiac hypertrophy, [32][33][34] but some report improvement post-transplant.…”
Section: Lvh Is the Most Common Cardiac Abnormality In Children With Ckdmentioning
confidence: 99%